VLSI Implementation of Speech Steganography with Advanced Wavelet Transform - Akhila, B.; Kareena, Shaik; Nikhitha, Makke; Sri, Valmeti Karuna; Shahina, Shaik (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
In the realm of secure communication systems, the integration of advanced wavelet transforms into speech steganography systems has emerged as a promising path. Secure transmission of sensitive information in military communications, confidential exchange of data in corporate environments, and protection of personal information in telecommunication networks. However, the current system employs conventional methods of speech steganography, relying on basic encryption techniques and simplistic embedding algorithms. While functional, these approaches lack robustness and fail to adequately conceal secret data within speech signals, leaving them vulnerable to detection and interception. So, the proposed system leverages advanced wavelet transforms to enhance the security and efficiency of speech steganography. By exploiting the multi-resolution analysis capabilities of wavelets, the system achieves improved embedding capacity while maintaining perceptual transparency. Additionally, the use of dynamic embedding algorithms based on wavelet coefficients ensures adaptability to varying signal characteristics, enhancing robustness against attacks and noise interference. The VLSI implementation of this system optimizes resource utilization and computational efficiency, making it suitable for real-time applications in communication systems.